Implementation Of Lean Manufacturing At Emerson Process Management Nilai Malaysia - Velayuthan, Sagar V. (2000)
The objective of the study is to understand the approach taken by Emerson Process Management in implementing Lean Manufacturing. The study would also analyse the outcome of its implementation and the challenges faced by the organization in the process of implementing this concept.